Proteomic profiling of the white shrimp Litopenaeus vannamei (Boone, 1931) hemocytes infected with white spot syndrome virus reveals the induction of allergy-related proteins. (February 2019) - Hernández-Pérez, Ariadne; Zamora-Briseño, Jesús Alejandro; Ruiz-May, Eliel; Pereira-Santana, Alejandro; Elizalde-Contreras, José Miguel; Pozos-González, Sirenia; Torres-Irineo, Edgar; Hernández-López, Jorge; Gaxiola-Cortés, Martha Gabriela; Rodríguez-Canul, Rossanna
Abstract: To elucidate the proteomic responses of shrimp hemocytes to white spot syndrome virus (WSSV) infection at the proteome level, a quantitative shotgun proteomic analysis was performed to detect differentially synthesized proteins in infected hemocytes of white shrimp ( Litopenaeus vannamei ). We identified 1528 proteins associated to 203 gene ontology (GO) categories. The most representative GO categories were regulation of cellular processes, organic substance metabolic processes and nitrogen compound metabolic processes. Most of the 83 detected up-regulated proteins are involved in DNA regulation and organization and cell signaling. In contrast, most of the 40 down-regulated proteins were related to immune defense processes, protein folding, and development. Differentially induced proteins were further analyzed at the transcript level by RT-qPCR to validate the results. This work provides new insights into the alterations of L. vannamei hemocytes at the protein level at 12 h post-infection with WSSV. Interestingly, several of the up-regulated proteins are allergy-related proteins in humans. Based on our results, we suggest a deeper analysis of the effects of this interaction on the regulation of allergy related-proteins as their up-regulation during WSSV could represent a threat to human health. Highlights: 1528 proteins of the L. vannamei hemocyte's proteome were identified at 12 phi. 123 proteins were differentially accumulated at 12 hpi with WSSV. 83 were up-regulated and 40 were down-regulated. Several allergy-related proteins were induced during WSSV infection.